Real time fault injection using on chip debug infrastructures: a case study - André Fidalgo (2006)
As electronic devices get smaller and more complex, dependability assurance is becoming fundamental for many mission critical computer based systems. This paper presents a case study on the possibility of using the on-chip debug infrastructures present in most current microprocessors to execute real time fault injection campaigns. The proposed methodology is based on a debugger customized for fault injection and consists of injecting bit-flip type faults on memory elements without modifying or halting the target application. Three different configurations are compared in terms of performance, area overhead and communication bus width. The basic debugger design is easily portable and applicable to different architectures, providing a flexible and efficient mechanism for verifying and validating fault tolerant components.